Cover Picture: High‐Speed Fabrication of Lithium‐Ion Battery Electrodes by UV‐Curing (Energy Technol. 5/2015). Issue 5 (May 2015) - Xue, Zheng; Hu, Libo; Amine, Khalil; Zhang, Zhengcheng
<x xml:space="preserve">Abstract</x> UV Radiation is the Cure: A high‐speed UV‐curing process to fabricate composite cathode laminates for lithium‐ion batteries is presented in the Communication on page 469 by Zhengcheng Zhang and colleagues at Argonne National Laboratory. A UV‐curable, multifunctional polysiloxane acrylate (PSA) is synthesized and demonstrated to be suitable as binder precursor for the fabrication of LiNi1/3Mn1/3Co1/3O2 (NMC) cathodes. In the presence of 10 wt% PSA binder, the mechanically robust NMC electrode laminate fabricated by UV‐curing exhibits very good mechanical properties and electrochemical performance in cell testing. This initial success in applying high‐speed UV‐curing in composite electrode fabrication proves that it is a promising route to substantially reducing the capital and operation costs of lithium‐ion battery electrode manufacturing and additionally bringing about important environmental benefits.